The role of oxidative stress in successful cryopreservation of south-west Western Australian plant species - Funnekotter, Bryn (Curtin University, 2015)
The southwest Western Australian Floristic region contains high plant diversity in need of conservation. Cryopreservation, the storage of plants in liquid nitrogen (-196°C), is the safest long-term conservation method available. However, there are many factors that can influence the plants ability to survive cryopreservation. Oxidative stress, which can damage DNA, proteins, and lipids, was shown to be a major factor affecting cryopreservation. Plants that mitigated excessive oxidative stress showed improved post-cryogenic survival.